A previously undescribed variant of a cervical rib structure related to a split cord malformation and review of the literature - Brittni Burgess; Christian Fisahn; Joe Iwanaga; Marc Moisi; Rod J. Oskouian; R. Shane Tubbs; Jason Cormier (Elsevier, 2016)
Introduction: Split cord malformation is a congenital condition that varies in form and severity, primarily diagnosed in pediatric patients. Surgical treatment is the most common method of correction. Herein, we discuss an extremely rare case of a split cord malformation associated with a midline cervical rib. Presentation of case: A 49-year-old male patient presented to the emergency department with cervical spine trauma. MRI and CT scans were performed of the patient, revealing an unknown cervical rib structure and underlying split cord malformation. Conclusion: To our knowledge, this is the first report of an anomalous midline cervical rib related to a split cord malformation. Such a finding should prompt the clinician to further evaluate such a patient for underlying congenital occult spinal dysraphism such as split cord malformation. Keywords: Cervical rib, Split cord malformation, Spine